Basic Math Examples

Solve for a d=(a+b)/(a-b)
d=a+ba-b
Step 1
Rewrite the equation as a+ba-b=d.
a+ba-b=d
Step 2
Find the LCD of the terms in the equation.
Tap for more steps...
Step 2.1
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
a-b,1
Step 2.2
Remove parentheses.
a-b,1
Step 2.3
The LCM of one and any expression is the expression.
a-b
a-b
Step 3
Multiply each term in a+ba-b=d by a-b to eliminate the fractions.
Tap for more steps...
Step 3.1
Multiply each term in a+ba-b=d by a-b.
a+ba-b(a-b)=d(a-b)
Step 3.2
Simplify the left side.
Tap for more steps...
Step 3.2.1
Cancel the common factor of a-b.
Tap for more steps...
Step 3.2.1.1
Cancel the common factor.
a+ba-b(a-b)=d(a-b)
Step 3.2.1.2
Rewrite the expression.
a+b=d(a-b)
a+b=d(a-b)
a+b=d(a-b)
Step 3.3
Simplify the right side.
Tap for more steps...
Step 3.3.1
Apply the distributive property.
a+b=da+d(-b)
Step 3.3.2
Rewrite using the commutative property of multiplication.
a+b=da-db
a+b=da-db
a+b=da-db
Step 4
Solve the equation.
Tap for more steps...
Step 4.1
Subtract da from both sides of the equation.
a+b-da=-db
Step 4.2
Subtract b from both sides of the equation.
a-da=-db-b
Step 4.3
Factor a out of a-da.
Tap for more steps...
Step 4.3.1
Factor a out of a1.
a1-da=-db-b
Step 4.3.2
Factor a out of -da.
a1+a(-d)=-db-b
Step 4.3.3
Factor a out of a1+a(-d).
a(1-d)=-db-b
a(1-d)=-db-b
Step 4.4
Divide each term in a(1-d)=-db-b by 1-d and simplify.
Tap for more steps...
Step 4.4.1
Divide each term in a(1-d)=-db-b by 1-d.
a(1-d)1-d=-db1-d+-b1-d
Step 4.4.2
Simplify the left side.
Tap for more steps...
Step 4.4.2.1
Cancel the common factor of 1-d.
Tap for more steps...
Step 4.4.2.1.1
Cancel the common factor.
a(1-d)1-d=-db1-d+-b1-d
Step 4.4.2.1.2
Divide a by 1.
a=-db1-d+-b1-d
a=-db1-d+-b1-d
a=-db1-d+-b1-d
Step 4.4.3
Simplify the right side.
Tap for more steps...
Step 4.4.3.1
Combine the numerators over the common denominator.
a=-db-b1-d
Step 4.4.3.2
Factor b out of -db-b.
Tap for more steps...
Step 4.4.3.2.1
Factor b out of -db.
a=b(-d)-b1-d
Step 4.4.3.2.2
Factor b out of -b.
a=b(-d)+b-11-d
Step 4.4.3.2.3
Factor b out of b(-d)+b-1.
a=b(-d-1)1-d
a=b(-d-1)1-d
Step 4.4.3.3
Factor -1 out of -d.
a=b(-(d)-1)1-d
Step 4.4.3.4
Rewrite -1 as -1(1).
a=b(-(d)-1(1))1-d
Step 4.4.3.5
Factor -1 out of -(d)-1(1).
a=b(-(d+1))1-d
Step 4.4.3.6
Simplify the expression.
Tap for more steps...
Step 4.4.3.6.1
Rewrite -(d+1) as -1(d+1).
a=b(-1(d+1))1-d
Step 4.4.3.6.2
Move the negative in front of the fraction.
a=-b(d+1)1-d
a=-b(d+1)1-d
a=-b(d+1)1-d
a=-b(d+1)1-d
a=-b(d+1)1-d
d=a+ba-b
(
(
)
)
|
|
[
[
]
]
π
π
7
7
8
8
9
9
4
4
5
5
6
6
/
/
^
^
×
×
>
>
!
!
1
1
2
2
3
3
-
-
+
+
÷
÷
<
<
,
,
0
0
.
.
%
%
=
=
 [x2  12  π  xdx ]